Дослідження спонтанної кристалізації алмаза в системах на основі магнію - Коваленко, Т.В.; Івахненко, С.О.; Білявина, Н.М.; Шульженко, О.О. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Experimental researches of diamond synthesis process in Mg – Zn – С and Mg – C systems have allowed to define optimal parameters of synthesis and to draw conclusions on an opportunity of use of these systems for synthesis by a temperature gradient method. It is shown, that in Mg – C system a new stable carbide is formed; on the basis of X-ray structure analysis its type was determined.